The duration and breadth of antibody responses to 3-dose of inactivated COVID-19 vaccinations in healthy blood donors: An observational study - Ou, Shanhai; Huang, Zehong; Lan, Miaoling; Ye, Jianghui; Chen, Jijin; Guo, Huilin; Xiao, Jin; Zhuang, Shucheng; Wu, Jiahuang; Yang, Chuanlai; Fang, Mujin; Su, Yingying; et al. (Frontiers in Immunology, 2022)
Objectives: We aimed to evaluate the duration and breadth of antibodies elicited by inactivated COVID-19 vaccinations in healthy blood donors. Methods: We performed serological tests on 1,417 samples from 658 blood donors who received two (n=357), or three (n=301) doses of COVID-19 inactivated vaccine. We also accessed the change in antibody response before and after booster vaccination in 94 participants and their neutralization breadth to the current variants after the booster. Results: Following vaccination, for either the 2- or 3-dose, the neutralizing antibodies (nAbs) peaked with about 97% seropositivity approximately within one month but subsequently decreased over time. Of plasmas collected 6-8 months after the last immunization, the nAb seropositivities were 37% and 85% in populations with 2-dose and 3-dose vaccinations, respectively. The nAbs of plasma samples (collected between 2-6 weeks after the 3rd dose) from triple-vaccinated donors (n=94) showed a geometric mean titer of 145.3 (95% CI: 117.2 to 180.1) against the ancestral B.1, slightly reduced by 1.7-fold against Delta variant, but markedly decreased by 4-6 fold in neutralizing Omicron variants, including the sub-lineages of BA.1 (5.6-fold), BA.1.1 (6.0-fold), BA.2 (4.2-fold), B.2.12.1 (6.2-fold) and BA.4/5 (6.5-fold). Conclusion: These findings suggested that the 3rd dose of inactivated COVID-19 vaccine prolongs the antibody duration in healthy populations, but the elicited-nAbs are less efficient in neutralizing circulating Omicron variants.